PROSPECT OF NON-TRADITIONAL TYPES OF DEPOSITS MINING IN THE WORLD OCEAN AND UKRAINIAN PART OF BLACK SEA (ON THE EXAMPLE OF GAS-HYDRATE) - POLOVKA, S. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2024)
The article presents the way non-traditional treasures of the soil (the so-called gas-hydrate). The Ukrainian scientists' achievements in this sphere have been described. The prospect chart of zone gasing in the Black Sea deep trench is created. The data of the depth and density of the gas-hydrate concentration are given.